Rural Pharmacy not delivering on its health promotion potential - Sunderland, Bruce; Burrows, Suzanne; Joyce, Andrew; McManus, Alexandra; Maycock, Bruce (Blackwell Publishing, 2006)
Objective: To investigate the level and perceived quality of health promotion advice received from rural pharmacists.Design: Self-administered written survey on access to and quality of pharmacy services in rural Western Australia completed by rural residents.Setting: Rural Pharmacy.Participants: Four hundred and eighty-three respondents who regularly used a pharmacy.Outcome measures: Items in the survey included frequency of receiving prevention advice and satisfaction ratings on health and pharmacy services.Results: Eighty-eight per cent of respondents had never discussed exercise or diet with their pharmacist and 65% had never discussed preventing health problems. Receiving good prevention advice predicted satisfaction with health services in general but not satisfaction with pharmacy services.Conclusion: Pharmacies are being underutilised with respect to their capacity to deliver heath prevention advice and ways to capitalise on this potential need to be investigated.